Labour-market polarisation and elementary occupations in Europe : Blip or long-term trend? - (:unkn) unknown (Publications Office of the European Union, 2011)
"European countries continue to experience significant changes in their economic and occupational structures, exposing workers and firms to rapidly evolving knowledge, skills and competence needs. From 1998 to 2008, an occupational polarisation emerged for the first time in Europe, with a concomitant rising demand at the upper and lower ends of the occupational skill distribution. In this paper, particular attention is given to elementary occupations. Much of the phenomenon can be traced back to macroeconomic trends and structural changes between sectors. The increasing labour supply of non-national workers, and some institutional characteristics, are also likely to be significant explanatory factors. In contrast, technological progress and/or work content changes seem to play a minor role. A more qualitative and institutionally oriented approach would contribute to better understanding of the phenomenon and to assessing whether a relative increase in elementary occupations will persist in the near future." (Hrsg., BIBB-Doku)
Keywords: P 2.2 An- und Ungelernte; G 2.3 Wandel von Arbeit & Wirtschaft; G 1.2 Arbeitsmarkt; G 1.3.3.3 Mobilität; I 2.2 Europa; Geringqualifizierter; Angelernter; Ungelernter; Berufsstrukturwandel; Wirtschaftsstrukturwandel; Arbeitsmarktsegmentation; Berufliche Mobilität; Europa